A Multidimensional Study of Absorptive Capacity and Innovation Capacity and Their Impact on Business Performance - Sancho-Zamora, Rafael; Gutiérrez-Broncano, Santiago; Hernández-Perlines, Felipe; Peña-García, Isidro (Frontiers in Psychology, 2021)
The aim of this paper is to understand how absorptive capacity and innovativeness influence business performance. Most previous studies have not considered the different dimensions of absorptive capacity and innovativeness. As a consequence, they have not analyzed the relationships between these dimensions, such as potential and realized absorptive capacity (RACAP) and product and process innovation. In our study, we analyzed the relationships between each of these dimensions and their effect on organizational performance. To achieve this, in addition to the theoretical foundation provided by the working hypotheses, a questionnaire was sent to 800 CEOs of Spanish companies in different sectors, obtaining a response rate of 38.25%. Structural equation modeling was applied to test the hypotheses. This study confirms the positive effect of absorptive capacity on innovation capacity, which in turn has a positive effect on business performance. Moreover, different dimensions of absorptive capacity and innovativeness play an important role in these relationships. This study contributes to a better understanding of how potential and RACAP influence the innovativeness of firms, both in their ability to innovate products and to improve business processes. In addition, it explores how these different innovations impact business performance and provide firms with knowledge on how to invest resources to increase profits. Future research should further study the inner workings of each of the dimensions analyzed to determine the importance of each dimension for business performance.